Trends in hospital antibiotic utilization during the coronavirus disease 2019 (COVID-19) pandemic: A multicenter interrupted time-series analysis. Issue 1 (28th July 2022) - Elligsen, Marion; Wan, Michael; Lam, Philip W.; Lo, Jennifer; Taggart, Linda R.; Chan, April J.; Downing, Mark; Gough, Kevin; Seah, Jenny; Leung, Elizabeth
Abstract: Objective: To describe the evolution of respiratory antibiotic prescribing during the coronavirus disease 2019 (COVID-19) pandemic across 3 large hospitals that maintained antimicrobial stewardship services throughout the pandemic. Design: Retrospective interrupted time-series analysis. Setting: A multicenter study was conducted including medical and intensive care units (ICUs) from 3 hospitals within a Canadian epicenter for COVID-19. Methods: Interrupted time-series analysis was used to analyze rates of respiratory antibiotic utilization measured in days of therapy per 1, 000 patient days (DOT/1, 000 PD) in medical units and ICUs. Each of the first 3 waves of the pandemic were compared to the baseline. Results: Within the medical units, use of respiratory antibiotics increased during the first wave of the pandemic (rate ratio [RR], 1.76; 95% CI, 1.38–2.25) but returned to the baseline in waves 2 and 3 despite more COVID-19 admissions. In ICU, the use of respiratory antibiotics increased in wave 1 (RR, 1.30; 95% CI, 1.16–1.46) and wave 2 of the pandemic (RR, 1.21; 95% CI, 1.11–1.33) and returned to the baseline in the third wave, which had the most COVID-19 admissions. Conclusions: After an initial surge in respiratory antibiotic prescribing, we observed the normalization of prescribing trends at 3 large hospitals throughout the COVID-19 pandemic. This trend may have been due to the timely generation of new research and guidelines developed with frontline clinicians, allowing for the active application of new research to clinical practice.